Pengaruh Promosi Video Marketing, Social Identity, dan Electronic Word of Mouth (E-WOM) Terhadap Keputusan Pembelian Konsumen Pada Marketplace Tokopedia - Jihad Muhammad Bandajati; Titik Desi Harsoyo (Economics Professional in Action (E-Profit), 2023)
The purpose of this study was to investigate how video marketing promotions, social identity, and electronic word of mouth influence consumer purchasing decisions on the Tokopedia marketplace. 100 people were selected to participate in this study as respondents. This study used a questionnaire as a research instrument and a survey as a data collection method. The instrument test shows that the research data is valid and reliable. In the classic assumption test it is stated that the information in this study is normally distributed and provides a regression model that is free from multicollinearity and heteroscedasticity. The results of this study indicate: 1) Video marketing has a positive and significant effect on consumer purchasing decisions on the Tokopedia Marketplace; 2) social identity has no impact on consumer purchasing decisions; and 3) electronic word of mouth has a positive and significant effect on consumer purchasing decisions on the Tokopedia Marketplace. The results of this study have implications for future researchers to study purchasing decisions using different subjects and objects.